THE USE OF RECOMBINATION ACTIVITY TO DEVELOP STUDENTS’ DISCOURSE SKILLS - Banatul Murtafi'ah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2020)
Discourse analysis cannot be neglected nor separated from our lives. Several experts even claim its importance in language teaching. The need to teach a language in context is something which is unavoidable. Therefore, a lesson plan to develop students’ discourse is needed. This paper reports on a result of teaching practice conducted at a language institution in Yogyakarta. The research was started from lesson plan development to teaching practice in the classroom. The lesson plan followed top-down approach and text-based approach on the model. It focused on the use of recombination activity. At the end of the lesson, three questions were given as a reflection for the students. The results show that half of the students succeeded in arranging the sentences into correct order for the recombination task. it was found that half of them agreed that title provision might help them in doing recombination activity. In addition, all of them also agreed that the knowledge of language features of the text helped them in doing recombination activity. They even mentioned that it was the knowledge of conjunctions that helped them in doing the activities. These results prove that the use of recombination activity may develop students’ discourse skills.Keywords: discourse analysis; recombination activity; lesson plan